Wolny Związkowiec . biuletyn Komitetu Strajkowgo HK, 08 November 1982 - Tymczasowa Komisja Koordynacyjna NSZZ "Solidarność" "Huty Katowice" (NSZZ "Solidarność" "Huta Katowice", 1982)
Creation and circulation: After introduction of the Martial Law on December 13, 1981 published underground. First published more than once a day as occupation edition, later irregularly. From issue no. 10(wrzesień 1989) published again legally